Hopes and Hurdles: Parents’ Perceptions and Experiences with Transition Planning for Students with Intellectual Disabilities - Robinson, Jason; Mueller, Tracy Gershwin (Journal of the American Academy of Special Education Professionals, 2020)
The Individuals with Disabilities Education Act (IDEA) mandates parents’ participation as a necessary component of providing an appropriate education to students with disabilities. Despite these guidelines, parents report challenges with joining and contributing to the individualized education program (IEP) team as equal and valuable educational partners. We used purposeful sampling techniques to interview ten parents about their perceptions, satisfaction, and experiences related to the postsecondary transition planning process for their child. Findings indicated the parents identified hopes and hurdles when planning for their child’s postsecondary life. The parents had hopes for individualized transition plans, high expectations, and collaborative practices characterized by mutual respect and open-mindedness during the planning process. Meanwhile, parents also reported hurdles that included experiencing conflict with professionals when advocating for their child, as well as uncertainty and apprehension for their child’s future. Each construct is discussed in detail, along with implications for practice and future research.